Teachers' Beliefs in Curriculum Innovation: Pre-Delphi Reflections of Secondary Curriculum Leaders - Al Musanna; Septia Wahyuni; Delfia Herwanis; Rahmanita Zakaria; Maulida Maulida; Suminah Suminah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study explores how senior secondary curriculum leaders interpret teachers' beliefs in curriculum innovation. A qualitative descriptive design was used with written reflective responses collected before a Delphi panel discussion. Participants were 60 vice principals for curriculum affairs from senior secondary schools in Aceh Tengah and Bener Meriah, Indonesia. The data were examined through thematic analysis involving familiarisation, open coding, categorisation, theme development, and peer debriefing. The findings identify three themes: moral commitment, professional resilience, and pedagogical guidance. Participants described teachers' beliefs as a source of responsibility toward students, a resource for maintaining motivation during policy change, and a reference for interpreting curriculum standards and selecting instructional strategies. The study contributes to research on curriculum reform by showing how beliefs operate before collective deliberation. It also extends existing work on teacher cognition by positioning beliefs as a moral, resilience, and pedagogical framework used by school-level curriculum leaders. The findings suggest that curriculum innovation needs professional development that engages teachers' values and reflective judgment, not only technical training.